Regional Impacts of Trade Liberalization Strategies in Brazil - Edson Paulo Domingues; Mauro Borges Lemos (European Regional Science Association (ERSA), 2004)
There is a great interest in free trade areas (FTA) in Brazil, predominantly in the context of a proposed Free Trade Area of the Americas (FTAA). In addition, a free trade area between MERCOSUR (the customs union involving Brazil, Argentina, Uruguay, and Paraguay) and the European Union has also been considered. In this paper, an interregional computable general equilibrium (CGE) model is used to analyze the long-run regional effects of alternative trade liberalization strategies on Brazil. The model provides a description of the Brazilian inter-regional economic system, divided into two regions - Sao Paulo and Other Regions in Brazil. One of its innovations is a full specification of foreign trade in both regions, capturing the complete structure of trade flows and import tariffs, linking the two Brazilian regions and a set of foreign markets. In this way, adequate simulations of tariff liberalization can be implemented for several possibilities of trade agreements.
Keywords: 330